Structural Modeling of Elementary School Teacher Turnover Intention In West Pasaman District, Indonesia - Rifma Rifma; Riki Batubara; Syahril Syahril; Irsyad Irsyad; Ranti Meizatri (Ta'dib, 2022)
We use the scale of job satisfaction, school culture, and organizational commitment to analyze their effect on the turnover intention of honorary primary school teachers. This study uses a quantitative approach with the ex post facto method and correlational study. The population in this study were honorary teachers of the West Pasaman Regency Elementary School who were recorded in 2021. Five representative sub-districts were selected, namely: (1) Luhak Nan Duo, (2) Talamau, (3) Sungau Aur, (4) Valley Transverse, and (5) Koto Balingka. Sampling was carried out using purposive and proportional random sampling techniques. Sample in this study amounted to 200 honorary teachers. The instrument in this study was developed using a Likert scale. SEM SmartPls data processing was used to analyze the hypothesis. The results showed that the variables of job satisfaction, school culture, and organizational commitment had an effect on the turnover intention of honorary teachers in the West Pasaman Regency. Thus, efforts to increase job satisfaction, school culture, and teacher organizational commitment are recommended to reduce turnover intention, especially for honorary teachers.